Risk factors for incident dementia after stroke and transient ischemic attack. Issue 1 (5th March 2014) - Yang, Jie; Wong, Adrian; Wang, Zhaolu; Liu, Wenyan; Au, Lisa; Xiong, Yunyun; Chu, Winnie W.C.; Leung, Eric Y.L.; Chen, Sirong; Lau, Christine; Chan, Anne Y.Y.; Lau, Alexander Y.L.; et al.
Abstract: Background: We hypothesized that chronic brain changes are important substrates for incident dementia after stroke and transient ischemic attack (TIA). Methods: We compared clinical and imaging features between patients with consecutive stroke/TIA with (n = 88) and without (n = 925) incident dementia at 3 to 6 months after a stroke/TIA. Pittsburg compound B (PiB) positron emission tomography was performed in 50 patients, including those with (n = 37) and without (n = 13) incident dementia. Results: Age, history of diabetes mellitus, severity of white matter changes (WMCs), and medial temporal lobe atrophy (MTLA) were associated with incident dementia. Alzheimer's disease (AD)–like PiB retention was found in 29.7% and 7.7% ( P  = .032) of patients with and without incident dementia, respectively. Conclusions: Chronic brain changes including WMCs, MTLA, and AD pathology are associated with incident dementia after stroke/TIA. Interventions targeting these chronic brain changes may reduce burden of vascular cognitive impairment.